Comparative study of conventional sliding mode control and integral sliding mode control for a bidirectional dc-dc converter in an electric vehicle charger - Oualifi Khadija; Abouobaida Hassan; Mchaouar Youssef; Fathelkhair Abdelmoghit; Akli Hajar; Abouelmahjoub Younes (E3S Web of Conferences)
Bidirectional dc-dc converters are crucial for integrating electric vehicles (EVs) with the electrical grid, facilitating both grid-to-vehicle (G2V) and vehicle to grid (V2G) energy transfers. Nonetheless, effectively controlling bidirectional energy flow poses significant challenges. This study compares two control methods, the conventional sliding mode controller (CSMC) and the integral sliding mode controller (ISMC), as applied to a bidirectional dc-dc converter. The dc-dc converter functions in two distinct modes: during grid to vehicle (G2V), it operates in buck mode to charge the battery using either constant current or constant voltage based on the battery’s voltage level; and during vehicle-to-grid (V2G), it switches to boost mode to discharge battery power into the grid at a constant current. The proposed controllers were simulated using MATLABK/Simulink and compared with a traditional linear PI controller. The simulation results highlight the efficiency and superiority of ISMC over both CSMC and PI control. In particular, ISMC offers superior performance in terms of response time and accuracy.